2010
DOI: 10.17221/65/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination after sanitation of food contact surfaces in dairy and meat processing plants

Abstract: Schlegelová J., Babák V., Holasová M., Konstantinová L., Necidová L., Šišák F., Vlková H., Roubal P., Jaglic Z. (2010): Microbial contamination after sanitation of food contact surfaces in dairy and meat processing plants. Czech J. Food Sci., 28: 450-461.The occurrence of listeria monocytogenes, Salmonella spp., Bacillus cereus, Staphylococcus spp., enterococcus spp., and escherichia coli in raw food materials, food products, and on food contact surfaces after sanitation was investigated during the period of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
9
24
0
Order By: Relevance
“…The focus on food serving trays and dining table tops is consistent with several other reported studies that included a microbial evaluation of FCS items (Cosby et al, 2008;Mazni, Toh, Mohd Faiz Foong, & Norazmir, 2013;Schlegelova et al, 2010). Using triplicates of each sample, the microbial assessment of total coliform was 36 (3 samples x 2 subjects x 1 parameter x 6 foodservice establishments).…”
Section: Methodssupporting
confidence: 76%
“…The focus on food serving trays and dining table tops is consistent with several other reported studies that included a microbial evaluation of FCS items (Cosby et al, 2008;Mazni, Toh, Mohd Faiz Foong, & Norazmir, 2013;Schlegelova et al, 2010). Using triplicates of each sample, the microbial assessment of total coliform was 36 (3 samples x 2 subjects x 1 parameter x 6 foodservice establishments).…”
Section: Methodssupporting
confidence: 76%
“…The microbial assessment focused on food serving trays and dining table tops. The choice of these samples is consistent with several other reported studies that have included a microbial evaluation of FCS items (Cosby et al, 2008;Mazni, Toh, Mohd Faiz Foong, & Norazmir, 2013;Schlegelova et al, 2010). Using triplicates of each sample, the microbial assessment of total coliform was 36 (3 samples x 2 subjects x 1 parameter x 6 foodservice establishments).…”
Section: Methodssupporting
confidence: 62%
“…So far, it has been reported that staphylococci may become endemic in the environment of abattoirs (Borch et al 1996), and several reports suggest that human S. aureus may become part of the endemic flora of food handlers, with subsequent contamination of carcasses and meat Desmarchelier et al 1999;Schlegelová 2004). In the study performed in the Czech Republic, S. aureus and S. epidermidis were isolated from food contact surfaces in dairy and meat processing plants (Schlegelová et al 2010).…”
Section: Resultsmentioning
confidence: 99%